النظام القانوني للقياسة في الجزائر - محمد أمين بلواعر; مصطفى ملوح (My University, 2018)
Summary: The theme of the measurement is "standardization", with provisions for uniform and frequent use in the face of real or potential problems that contain solutions to technical and commercial problems related to products, goods and services frequently raised in relations between economic, scientific, technical and social partners. products ", thus playing a significant role in defining the characteristics of products and services on the market. The measurement "standardization" is mainly aimed at ensuring the harmonization and compatibility of products as well as playing a significant role in facilitating international trade, these general objectives have broadened its scope to include other objectives of primary interest to the consumer At present, it is looking for solutions to bring products and services into line with the consumer's wishes. Without prejudice to his health and security, he also aims to protect the environment as living in the environment is a fundamental right. .................... الملخص : يتمثل موضوع القياسة" التقييس" في وضع أحكام ذات إستعمال موحد و متكرر في مواجهة مشاكل حقيقة أو محتملة تحتوي على حلول لمشاكل تقنية و تجارية تخص المنتوجات و السلع و الخدمات التي تطرح بصفة متكررة في العلاقات بين الشركاء الإقتصاديين و العلميين و التقنيين و الإجتماعيين، إذن فهو يلعب دورا معتبرا في تحديد خصائص المنتوجات و الخدمات المعروضة في الأسواق. يهدف القياسة "التقييس" أساسا إلى ضمان إنسجام المنتوجات و توافقها، كما يلعب دورا معتبرا في تسهيل المبادلات التجارية الدولية، إن هذه الأهداف العامة أدت إلى إتساع نطاقه ليشمل أهداف أخرى تهم أساسا المستهلك، فهو في الوقت الحالي يبحث عن إيجاد حلول للوصول إلى مطابقة المنتوجات و الخدمات لرغبات المستهلك، و من دون أن تضر بصحته و أمنه، كما يهدف كذلك إلى حماية البيئة نظرا لأن العيش في البيئة نقية و صحية هو من الحقوق الأساسية. ...................... Résumé : Le thème de la mesure est la "normalisation", avec des dispositions pour une utilisation uniforme et fréquente face à des problèmes réels ou potentiels qui contiennent des solutions aux problèmes techniques et commerciaux liés aux produits, les biens et services fréquemment soulevés dans les relations entre les partenaires économiques, scientifiques, techniques et sociaux. produits ", jouant ainsi un rôle important dans la définition des caractéristiques des produits et services sur le marché. La mesure "normalisation" vise principalement à assurer l’harmonisation et la compatibilité des produits ainsi qu’à jouer un rôle important dans la facilitation du commerce international, Ces objectifs généraux ont élargi son champ d’application pour inclure d’autres objectifs d’intérêt primaire pour le consommateur. Sans préjudice de sa santé et de sa sécurité, il vise également à protéger l’environnement car la vie dans l’environnement est un droit fondamental.